PROSPECT AND PROMISE IN INTEGRATING MULTILITERACY PEDAGOGY IN THE ENGLISH LANGUAGE CLASSROOM IN INDONESIA - M Arinal Rahman; Melliyani Melliyani; Ciptro Handrianto; Erma Erma; Shahid Rasool (ETERNAL (English, Teaching, Learning and Research Journal), 2022)
This article discusses the multiliteracy idea to give reasons in favor of multiliteracy implementation in Indonesian classrooms. Multiliteracy offers fresh perspectives on language education and learning. The usage of multiliteracy in Indonesia provides potential benefits, such as the growth of pupils' literacy levels. Multiliteracy adds a new dimension to education and allows instructors to take an alternative approach to teach, moving away from the conventional teacher-centered method towards a more student-centered approach. Furthermore, it places the emphasis on critical thinking, cultural awareness, and fresh insight. Students are encouraged and expected to be more curious when studying multiliteracy since they will be able to explore and learn on their own. Educators in Indonesia, on the other hand, should not be unfamiliar with the notion of multiliteracy. It should be welcomed, and while it may appear challenging at first, it can be a rewarding and exciting experience for instructors and students.